ANGELTVEIT and MCKAY. Issue 1 (5th February 2018) - Angeltveit, Vigleik; McKay, Brendan D.
Abstract: We improve the upper bound on the Ramsey number R (5, 5) from R ( 5, 5 ) ≤ 49 to R ( 5, 5 ) ≤ 48 . We also complete the catalog of extremal graphs for R (4, 5).